Ti3SiC2-containing SiC fiber and preparation method thereof
By using a spinning precursor of polycarbosilane precursor, a titanium source and an additive, SiC fibers containing Ti3SiC2 were prepared, which solved the problem of insufficient conductivity and wave absorption performance of SiC fibers and achieved significant improvement in performance.
Patent Information
- Application Number
- CN202411653837.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to effectively introduce the Ti3SiC2 structure into SiC fibers, resulting in insufficient conductivity, electromagnetic absorption and oxidation resistance of SiC fibers.
Polycarbosilane precursors, titanium sources and additives are used as spinning precursors, and SiC fibers containing Ti3SiC2 are prepared in situ through spinning, non-melting and high-temperature sintering processes.
It significantly improves the conductivity, wave absorption and oxidation resistance of SiC fibers, making them suitable for applications such as conductivity, wave absorption and electromagnetic shielding.
Smart Images

Figure CN119430948A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic fibers and relates to a SiC fiber containing Ti3SiC2 and a preparation method thereof. Background Art
[0002] Silicon carbide (SiC) fibers have high strength (1-4 GPa), high modulus (150-400 GPa), low density (<3.5 g / cm 3 ), corrosion resistance and creep resistance. More importantly, it has excellent high temperature resistance, oxidation resistance and neutron irradiation resistance. Therefore, SiC fiber is mainly used as a reinforcement for high temperature resistant and radiation resistant composite materials, such as advanced aerospace structural components, high temperature engine components, gas turbine hot end components, high temperature gas, heat exchangers, nuclear cladding materials and other fields. The resistivity of general SiC fiber is 10 6 About Ω·cm, it is a typical microwave transparent material.
[0003] Ti3SiC2 is a widely studied MAX phase material. Due to its good thermal shock resistance, oxidation resistance, radiation resistance, electrical conductivity, lubricity and mechanical properties, it can be widely used as electrical contact material, heat exchanger component material, lubricating material, radioactive material cladding material, wave absorbing material, etc. in the future. The traditional preparation method of Ti3SiC2 is to prepare Ti, Si, C powder or Ti, SiC, C powder or TiC, Si, C powder by powder sintering method; common preparation methods include: pressureless sintering, hot pressing sintering, hot isostatic pressing, spark plasma sintering (SPS), molten salt method, etc. However, these methods are not suitable for the preparation of fiber materials, fiber-reinforced ceramic matrix composites, etc.
[0004] Some researchers have introduced metal elements such as titanium and zirconium into SiC fibers. For example, Yamamura et al. (Journal of Materials Science, 1988, 23: 2589-2594) used polydimethylsilane (PDMS) and butyl titanate to prepare polytitanium carbosilane (PTCS). PTCS was melt-spun and continuously heat-treated to prepare SiC (Ti) fibers. The resistivity of this fiber can be reduced to as low as 10 -1 Ω·cm; Ishikawa et al. (Journal of Materials Science, 1998, 33:161-166) used polycarbosilane (PCS) and zirconium acetylacetonate to synthesize polyzirconium carbosilane and prepared SiC (Zr) fibers; Yamamura (US5094907) used a resistivity of 10 -2 ~10 2The composite material made of SiC (containing Ti or Zr) fiber with a thickness of Ω·cm has a reflection attenuation of more than 15dB for 8-12GHz radar waves, and can reach a maximum of 40dB.
[0005] Introducing Ti3SiC2 structure into SiC fiber is beneficial to improving the conductivity, electromagnetic absorption, anti-oxidation and other properties of SiC fiber, but it is currently difficult to prepare SiC fiber containing Ti3SiC2. Summary of the invention
[0006] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a SiC fiber containing Ti3SiC2 in which the Ti3SiC2 structure is introduced into the SiC fiber. The SiC fiber is made by spinning, infusibility and high-temperature sintering a spinning precursor including a polycarbosilane precursor, a titanium source and an auxiliary agent, thereby effectively improving the performance of the SiC fiber.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A SiC fiber containing Ti3SiC2 is prepared by spinning, infusibility and high-temperature sintering a spinning precursor comprising a polycarbosilane precursor, a titanium source and an auxiliary agent.
[0009] Preferably, the Ti3SiC2 in the SiC fiber containing Ti3SiC2 is a MAX phase.
[0010] Preferably, the molecular main chain of the polycarbosilane precursor contains CH3SiHCH2 structural units and is solid at room temperature.
[0011] Preferably, the polycarbosilane precursor comprises one or more of polycarbosilane and polycarbosilane containing heterogeneous elements; the heterogeneous elements comprise one or more of aluminum, yttrium, nickel, hafnium, lithium, iron, cobalt, lanthanum, zirconium, titanium, beryllium, magnesium, calcium, vanadium and boron.
[0012] Preferably, the titanium source includes one or more of nano-Ti powder, TiH2 powder, TiC powder, TiN powder, and TiO2 powder, and the particle size is 5 to 500 nm.
[0013] More preferably, the average particle size of the titanium source is 5 to 300 nm.
[0014] Preferably, the auxiliary agent includes one or more of nano-Al powder, nano-Mg powder, nano-CaF2 powder, nano-Zn powder, nano-Cu powder and nano-Ag powder, and the particle size is 5 to 500 nm.
[0015] More preferably, the average particle size of the auxiliary agent is 5 to 300 nm.
[0016] Preferably, the solvent includes one or more of acetone, xylene, tetrahydrofuran, ethanol, n-hexane, dimethylformamide, and dimethylacetamide.
[0017] Preferably, in the spinning precursor, the titanium source accounts for 1 to 70% of the mass of the polycarbosilane precursor, and the auxiliary agent accounts for 0.5 to 20% of the mass of the titanium source.
[0018] Preferably, the strength of the SiC fiber containing Ti3SiC2 is ≥1.5GPa and the modulus is ≥150GPa; after electrical performance testing, the conductivity of the SiC fiber containing Ti3SiC2 is ≥2000S / m; after vector network analyzer testing of wave absorption performance, the minimum value of reflection loss RL of the SiC fiber containing Ti3SiC2 is ≤-8dB.
[0019] Further preferably, the strength of the SiC fiber containing Ti3SiC2 is ≥2.2GPa, and the modulus is ≥2200GPa; after electrical performance testing, the conductivity of the SiC fiber containing Ti3SiC2 is ≥6000S / m; after testing the wave absorption performance with a vector network analyzer, the minimum value of the reflection loss RL of the SiC fiber containing Ti3SiC2 is ≤-15dB.
[0020] A method for preparing SiC fiber containing Ti3SiC2, the preparation method comprising:
[0021] (1) Spinning: Spinning a spinning precursor including a polycarbosilane precursor, a titanium source, and an auxiliary agent to obtain a precursor fiber;
[0022] (2) Infusibility: The precursor fiber in (1) is infusible to obtain infusible fiber;
[0023] (3) High temperature sintering: The infusible fibers in (2) are sintered at high temperature in a protective atmosphere to obtain SiC fibers containing Ti3SiC2.
[0024] Preferably, the titanium source includes one or more of nano-Ti powder, TiH2 powder, TiC powder, TiN powder, and TiO2 powder, and the average particle size is 5 to 500 nm.
[0025] More preferably, the average particle size of the titanium source is 5 to 300 nm.
[0026] Preferably, the auxiliary agent includes one or more of nano-Al powder, nano-Mg powder, nano-CaF2 powder, nano-Zn powder, nano-Cu powder and nano-Ag powder, and the average particle size is 5 to 500 nm.
[0027] More preferably, the particle size of the auxiliary agent is 5 to 300 nm.
[0028] Preferably, in the spinning precursor, the titanium source accounts for 1 to 70% of the mass of the polycarbosilane precursor, and the auxiliary agent accounts for 0.5 to 20% of the mass of the titanium source.
[0029] Preferably, the polycarbosilane precursor comprises one or more of polycarbosilane and polycarbosilane containing heterogeneous elements; the heterogeneous elements comprise one or more of aluminum, yttrium, nickel, hafnium, lithium, iron, cobalt, lanthanum, zirconium, titanium, beryllium, magnesium, calcium, vanadium and boron.
[0030] Preferably, the diameter of the precursor fiber is 0.05-50 μm.
[0031] Preferably, the spinning includes one or more of melt spinning, dry spinning and electrospinning.
[0032] Further preferably, the melt spinning includes mixing the spinning precursor in a ball mill, placing it in a spinning barrel, heating it to 100-350° C. under an inert atmosphere, spinning it through a spinneret under a pressure of 0.1-10 MPa, and collecting it through a spinning drum to obtain precursor fibers.
[0033] Further preferably, the melt spinning includes: mixing a spinning precursor with a solvent to prepare a spinning solution, rotary evaporating the spinning solution to remove the solvent, placing it in a spinning cylinder, heating it to 100-350°C under an inert atmosphere, spinning through a spinneret under a pressure of 0.1-10 MPa, and collecting it through a spinning drum to obtain a precursor fiber.
[0034] More preferably, the solvent includes one or more of acetone, xylene, tetrahydrofuran, ethanol, n-hexane, dimethylformamide, and dimethylacetamide.
[0035] Further preferably, the dry spinning includes: under the protection of an inert atmosphere, mixing a spinning precursor with a solvent to prepare a spinning solution, placing the spinning solution in a spinning device, heating it to 50-150°C, keeping it warm for 0.5-5h, spinning through a spinneret under a pressure of 0.1-10MPa, and collecting it through a spinning drum to obtain a precursor fiber.
[0036] More preferably, the solvent includes one or more of acetone, xylene, tetrahydrofuran, ethanol, n-hexane, dimethylformamide, and dimethylacetamide.
[0037] More preferably, the solid content of the spinning solution is 40 to 80%.
[0038] Further preferably, the electrospinning includes: mixing a spinning precursor with a solvent to prepare a spinning solution, placing the spinning solution in an electrospinning machine jet device, the spinning voltage is 10 to 20 kV, the distance between the spinneret and the collector is 5 to 40 cm, and the spinning speed is 10 to 50 μL / min to obtain precursor fibers.
[0039] More preferably, the solvent includes one or more of acetone, xylene, tetrahydrofuran, ethanol, n-hexane, dimethylformamide, and dimethylacetamide.
[0040] More preferably, the solid content of the spinning solution is 40 to 80%.
[0041] Preferably, the infusibility treatment comprises one or both of air infusibility treatment and electron beam cross-linking treatment.
[0042] More preferably, the temperature at which the air does not melt is 150 to 250° C., the time is 1 to 20 hours, and the atmosphere is flowing air.
[0043] More preferably, the total radiation dose of the electron beam cross-linking is 2 to 20 Mgy, the time is 1 min to 10 h, and the atmosphere is a flowing protective atmosphere.
[0044] Preferably, the high temperature sintering temperature is 800-1600° C., the time is 0.1-10 h, and the protective atmosphere includes nitrogen atmosphere, inert atmosphere, or a combination of the two.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] 1. The present invention uses polycarbosilane precursor, titanium source and auxiliary agent as spinning precursors, and prepares SiC fiber material containing Ti3SiC2 in situ through spinning, infusibility and high-temperature sintering processes.
[0047] 2. The present invention introduces Ti3SiC2 structure into SiC fiber, which is beneficial to improving the electrical conductivity and wave absorbing performance of SiC fiber.
[0048] 3. The preparation method of the SiC fiber containing Ti3SiC2 of the present invention is simple and controllable, and the SiC fiber containing Ti3SiC2 can be extended to the application fields of electrical conduction, wave absorption, electromagnetic shielding, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 It is the infrared spectrum of PCS in Example 1 of the present invention.
[0050] Figure 2 This is the XRD spectrum of Ti3SiC2 / SiC fiber 1 in Example 1 of the present invention.
[0051] Figure 3 It is a low-magnification scanning electron microscope image of the Ti3SiC2 / SiC fiber 1 in Example 1 of the present invention.
[0052] Figure 4 It is a high-magnification scanning electron microscope image of the Ti3SiC2 / SiC fiber 1 in Example 1 of the present invention. DETAILED DESCRIPTION
[0053] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not used to specifically limit the present invention.
[0054] Unless otherwise specified, the materials used in the present invention are commercially available raw materials commonly used in the art, and the methods used are conventional technical means in the art.
[0055] Example 1
[0056] The preparation method of SiC fiber containing Ti3SiC2 in this embodiment is as follows:
[0057] Take 4g of polycarbosilane (PCS), add 2.6g of xylene, 0.65g of acetone, 1g of TiH2 powder and 0.1g of nano-aluminum powder, mix, stir and ultrasonically dissolve to obtain a spinning solution; electrospin the spinning solution to obtain PCS-Ti01 precursor fiber; the spinning conditions are: the inner diameter of the spinneret is 0.8mm, the spinning voltage is 16kV, the distance between the spinneret and the collector is 15cm, and the feeding speed is 30μL / min;
[0058] The PCS-Ti01 precursor fiber was placed in a vacuum drying oven, heated to 60°C and kept warm for 8 hours to remove the solvent; then placed in a tubular furnace, heated to 170°C at 2°C / min and kept warm for 3 hours under air atmosphere protection, and air-infusible PCS-Ti01 infusible fiber was obtained;
[0059] The PCS-Ti01 infusible fiber was placed in a high-temperature furnace, and under the protection of an argon atmosphere, the temperature was raised to 1200°C at a rate of 2°C / min, and kept at this temperature for 1 hour to obtain SiC nanofiber 1 containing Ti3SiC2, which was recorded as Ti3SiC2 / SiC fiber 1.
[0060] Figure 1 is the infrared spectrum of polycarbosilane in this embodiment; Figure 2 This is the XRD spectrum of Ti3SiC2 / SiC fiber 1. It can be seen that the product obtained in this embodiment contains Ti3SiC2, that is, the product of this embodiment is SiC nanofiber containing Ti3SiC2.
[0061] Figure 3is a low-magnification SEM photograph of the prepared Ti3SiC2 / SiC fiber 1; Figure 4 : is a high-magnification SEM photograph of the Ti3SiC2 / SiC fiber 1. It can be seen that the surface of the Ti3SiC2 / SiC fiber 1 prepared in this embodiment is smooth, and the average diameter of the Ti3SiC2 / SiC fiber 1 is 2 μm.
[0062] Example 2
[0063] The preparation method of SiC fiber containing Ti3SiC2 in this embodiment is as follows:
[0064] Take 20g of polycarbosilane (PCS), add 10g of xylene, 3g of acetone, 5g of TiH2 powder and 0.5g of nano magnesium powder, mix, stir and ultrasonically dissolve to obtain a spinning solution; dry-spin the spinning solution to obtain PCS-TiO2 precursor fiber. The dry spinning conditions are as follows: under the protection of argon atmosphere, place the spinning solution in a spinning device and raise the temperature to 80°C, keep it warm for 0.5h, and spray it out through the spinneret with argon gas. The argon gas pressure is 0.3MPa.
[0065] The PCS-TiO2 precursor fiber was placed in a vacuum drying oven, heated to 60°C and kept warm for 8 hours to remove the solvent; then placed in a tubular furnace, heated to 170°C at 2°C / min and kept warm for 3 hours under air atmosphere protection, and air-infusible PCS-TiO2 infusible fiber was obtained;
[0066] The PCS-Ti02 infusible fiber was placed in a high-temperature furnace, and under the protection of an argon atmosphere, the temperature was raised to 1200°C at a rate of 2°C / min, and kept at this temperature for 1 hour to obtain SiC fiber 2 containing Ti3SiC2, which was recorded as Ti3SiC2 / SiC fiber 2.
[0067] After the mechanical properties test, the strength of Ti3SiC2 / SiC fiber 2 was 2.0GPa and the modulus was 220GPa; after the electrical properties test, the conductivity of Ti3SiC2 / SiC fiber 2 was 8000S / m; after the vector network analyzer test of the wave absorption performance, the minimum reflection loss RL was -16dB.
[0068] Example 3
[0069] The preparation method of SiC fiber containing Ti3SiC2 in this embodiment is as follows:
[0070] Take 4g of polycarbosilane (PCS), add 4g of xylene, 1g of Ti powder, and 0.1g of nano-CaF2 powder, mix, stir, and ultrasonically dissolve, then place in a rotary evaporator to remove most of the solvent, and remove excess solvent in a vacuum oven at 100°C under vacuum conditions to obtain a PCS-Ti03 spinning precursor; then melt spinning is performed to obtain PCS-Ti03 precursor fibers; the melt spinning process is as follows: the PCS-Ti03 spinning precursor is loaded into a melt spinning barrel, and the spinning parameters are adjusted, the spinning parameters are: spinning temperature 300°C, spinning pressure 0.5MPa; melt spinning into PCS-Ti03 precursor fibers;
[0071] The PCS-TiO3 precursor fiber was placed in an electron irradiation device, and irradiated with a dose of 10 Mgy under an inert atmosphere for 0.5 h to obtain PCS-TiO3 infusible fiber.
[0072] The PCS-Ti03 infusible fiber was placed in a high-temperature furnace, and under the protection of an argon atmosphere, the temperature was raised to 1200°C at a rate of 2°C / min, and kept at this temperature for 1 hour to obtain SiC fiber 3 containing Ti3SiC2, which was recorded as Ti3SiC2 / SiC fiber 3.
[0073] After the mechanical property test, the strength of Ti3SiC2 / SiC fiber 3 was 2.3GPa and the modulus was 240GPa; after the electrical property test, the conductivity of Ti3SiC2 / SiC fiber 3 was 10000S / m; after the vector network analyzer test of the wave absorption performance, the minimum reflection loss RL was -18dB.
[0074] Example 4
[0075] The preparation method of SiC fiber containing Ti3SiC2 in this embodiment is as follows:
[0076] Take 20g of aluminum-containing polycarbosilane (PACS), add 12g of tetrahydrofuran, 3g of ethanol, 5g of TiC powder, and 0.6g of nano Zn powder, mix, stir, and ultrasonically dissolve to obtain a spinning solution; dry-spin the spinning solution to obtain PACS-TiO4 precursor fiber, and the dry spinning conditions are: under the protection of argon atmosphere, raise the spinning solution to 80°C in the spinning device, keep it warm for 0.5h, and spray it out through the spinneret with argon gas, and the argon gas pressure is 0.5MPa;
[0077] The PACS-Ti04 precursor fiber was placed in a vacuum drying oven, heated to 80°C and kept for 6 hours to remove the solvent; then placed in an electron beam irradiation device, irradiated with a dose of 10 Mgy under an inert atmosphere, and cross-linked by electron beam irradiation to obtain PCS-Ti04 infusible fiber;
[0078] The PCS-Ti04 infusible fiber was placed in a high-temperature furnace, and under the protection of an argon atmosphere, the temperature was raised to 1400°C at a rate of 2°C / min, and kept at this temperature for 1 hour to obtain SiC fiber 4 containing Ti3SiC2, which was recorded as Ti3SiC2 / SiC fiber 4.
[0079] After the mechanical property test, the strength of SiC fiber 4 containing Ti3SiC2 was 2.5GPa and the modulus was 260GPa; after the electrical property test, the conductivity of SiC fiber 4 containing Ti3SiC2 was 11000S / m; after the vector network analyzer test of the wave absorption performance, the minimum value of the reflection loss RL was -20dB.
[0080] Example 5
[0081] The preparation method of SiC fiber containing Ti3SiC2 in this embodiment is as follows:
[0082] Take 4g of zirconium-containing polycarbosilane (PZCS), add 3.3g of n-hexane, 1.09g of dimethylformamide, 1g of TiC powder, and 0.1g of nano Zn powder, mix, stir, and ultrasonically dissolve to obtain a spinning solution; electrospin the spinning solution to obtain PZCS-Ti05 precursor fiber, and the spinning conditions are: the inner diameter of the spinneret is 0.8mm, the spinning voltage is 18kV, the distance between the spinneret and the collector is 15cm, and the feed rate is 40μL / min;
[0083] The PZCS-Ti05 precursor fiber was placed in a vacuum drying oven, heated to 120°C and kept for 3 hours to remove the solvent; then placed in a tubular furnace, heated to 180°C at 2°C / min and kept for 3 hours under air atmosphere protection to perform air infusibility, thereby obtaining PCS-Ti05 infusible fiber;
[0084] The PCS-Ti05 infusible fiber was placed in a high-temperature furnace, and under the protection of an argon atmosphere, the temperature was raised to 1200°C at a rate of 2°C / min, and kept at this temperature for 1 hour to obtain SiC nanofiber 5 containing Ti3SiC2, which was recorded as Ti3SiC2 / SiC fiber 5.
[0085] Example 6
[0086] The preparation method of SiC fiber containing Ti3SiC2 in this embodiment is as follows:
[0087] Take 20g of iron-containing polycarbosilane (PFCS), add 14g of n-hexane, 4g of dimethylacetamide, 5g of TiC powder, and 1.0g of nano-Cu powder, mix, stir, and ultrasonically dissolve to obtain a spinning solution; dry-spin the spinning solution to obtain PFCS-Ti06 precursor fiber, and the dry spinning conditions are: under the protection of argon atmosphere, place the spinning solution in a spinning device and raise it to 80°C, keep it warm for 0.5h, and spray it out through the spinneret with argon gas, and the argon gas pressure is 0.6MPa;
[0088] The PFCS-Ti06 precursor fiber was placed in an electron beam irradiation device, irradiated with a dose of 15 Mgy under an inert atmosphere, and crosslinked by electron beam irradiation for 1 h to obtain PCS-Ti06 infusible fiber;
[0089] The PCS-Ti06 infusible fiber was placed in a high-temperature furnace, and under the protection of an argon atmosphere, the temperature was raised to 1500°C at a rate of 2°C / min, and kept at this temperature for 1 hour to obtain SiC fiber 6 containing Ti3SiC2, which was recorded as Ti3SiC2 / SiC fiber 6.
[0090] After the mechanical properties test, the strength of Ti3SiC2 / SiC fiber 6 was 2.8GPa and the modulus was 280GPa; after the electrical properties test, the conductivity of Ti3SiC2 / SiC fiber 6 was 12000S / m; after the vector network analyzer test of the wave absorption performance, the minimum reflection loss RL was -30dB.
[0091] Example 7
[0092] The preparation method of SiC fiber containing Ti3SiC2 in this embodiment is as follows:
[0093] Take 4g of yttrium-containing polycarbosilane (PYCS), add 3.3g of n-hexane, 1.09g of dimethylformamide, 1g of TiN powder and 0.1g of nano-Cu powder, mix, stir and ultrasonically dissolve to obtain a spinning solution; electrospin the spinning solution to obtain PCS-Ti07 precursor fiber, and the spinning conditions are: the inner diameter of the spinneret is 0.8mm, the spinning voltage is 13kV, the distance between the spinneret and the collector is 15cm, and the feed rate is 20μL / min;
[0094] The PYCS-Ti07 precursor fiber was placed in a vacuum drying oven, heated to 100°C and kept for 5 hours to remove the solvent; then placed in a tube furnace, heated to 200°C at 2°C / min under air atmosphere protection and kept for 3 hours to perform air infusibility treatment, thereby obtaining PCS-Ti07 infusible fiber;
[0095] The PCS-Ti07 infusible fiber was placed in a high-temperature furnace, and under the protection of an argon atmosphere, the temperature was raised to 1300°C at a rate of 2°C / min and kept at this temperature for 1 hour to obtain SiC nanofiber 7 containing Ti3SiC2, which was recorded as Ti3SiC2 / SiC fiber 7.
[0096] Example 8
[0097] The preparation method of SiC fiber containing Ti3SiC2 in this embodiment is as follows:
[0098] Take 20g of boron-containing polycarbosilane (PBCS), add 14g of n-hexane, 5g of TiN powder and 0.5g of nano-Ag powder, mix, stir and ultrasonically dissolve, then place on a rotary evaporator to remove most of the solvent, remove excess solvent in a vacuum oven at 100°C under vacuum conditions to obtain a spinning precursor PCS-Ti08; then melt spinning is performed to obtain PCS-Ti08 precursor fibers; the melt spinning process is as follows: the spinning precursor PCS-Ti08 is loaded into a melt spinning barrel, and the spinning parameters are adjusted, the spinning parameters are: spinning temperature 310°C, spinning pressure 0.6MPa; melt spinning into PCS-Ti08 precursor fibers;
[0099] The PBCS-Ti08 precursor fiber was placed in a tubular furnace, and under the protection of air atmosphere, the temperature was raised to 210°C at 2°C / min and kept at this temperature for 4 hours to perform air infusibility treatment, thereby obtaining PCS-Ti08 infusible fiber.
[0100] The PCS-Ti08 infusible fiber was placed in a high-temperature furnace, and under the protection of an argon atmosphere, the temperature was raised to 1600°C at a rate of 2°C / min, and kept at this temperature for 1 hour to obtain SiC fiber 8 containing Ti3SiC2, which was recorded as Ti3SiC2 / SiC fiber 8.
[0101] After the mechanical property test, the strength of Ti3SiC2 / SiC fiber 8 was 1.5GPa and the modulus was 290GPa; after the electrical property test, the conductivity of Ti3SiC2 / SiC fiber 8 was 9000S / m; after the vector network analyzer test of the wave absorption performance, the minimum reflection loss RL was -15dB.
[0102] Comparative Example 1
[0103] The preparation method of SiC fiber in this comparative example is as follows:
[0104] Take 20g of polycarbosilane, add 10g of xylene and 3g of acetone respectively to prepare a spinning solution; dry-spin the spinning solution to obtain polycarbosilane precursor fiber, and the dry-spinning conditions are as follows: under the protection of argon atmosphere, raise the spinning solution to 80°C in the spinning device, keep it warm for 0.5h, and spray it through the spinneret with argon gas, and the argon gas pressure is 0.3MPa;
[0105] The PCS precursor fiber was placed in a vacuum drying oven, heated to 60°C and kept warm for 8 hours to remove the solvent; then placed in a tube furnace, heated to 170°C at 2°C / min and kept warm for 3 hours under air atmosphere protection to perform air infusibility, thereby obtaining PCS infusible fiber;
[0106] The PCS infusible fiber was placed in a high-temperature furnace, and under the protection of an argon atmosphere, the temperature was raised to 1200°C at a rate of 2°C / min, and kept at this temperature for 1 hour to obtain SiC fiber 1.
[0107] According to the mechanical property test, the strength of SiC fiber 1 is 2.1 GPa and the modulus is 210 GPa; according to the electrical property test, the conductivity of SiC fiber 1 is 60 S / m; and according to the wave absorption performance test using a vector network analyzer, the minimum reflection loss RL is -6 dB.
[0108] In summary, the present invention uses polycarbosilane precursor, titanium source and auxiliary agent as spinning precursors, and prepares SiC fiber material containing Ti3SiC2 in situ through spinning, infusibility and high-temperature sintering processes; and improves the conductivity, electromagnetic absorption, anti-oxidation and other properties of SiC fiber.
[0109] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A SiC fiber containing Ti3SiC2, characterized in that: The SiC fiber containing Ti3SiC2 is prepared by spinning, infusibility and high-temperature sintering a spinning precursor including a polycarbosilane precursor, a titanium source and an auxiliary agent.
2. The SiC fiber containing Ti3SiC2 according to claim 1, characterized in that The molecular main chain of the polycarbosilane precursor contains CH3SiHCH2 structural units and is solid at room temperature; the polycarbosilane precursor includes one or more of polycarbosilane and polycarbosilane containing heterogeneous elements, and the heterogeneous elements include one or more of aluminum, yttrium, nickel, hafnium, lithium, iron, cobalt, lanthanum, zirconium, titanium, beryllium, magnesium, calcium, vanadium, and boron.
3. The SiC fiber containing Ti3SiC2 according to claim 1, characterized in that The titanium source includes one or more of nano-Ti powder, TiH2 powder, TiC powder, TiN powder and TiO2 powder, and the average particle size is 5 to 500 nm.
4. The SiC fiber containing Ti3SiC2 according to claim 1, characterized in that The auxiliary agent comprises one or more of nano Al powder, nano Mg powder, nano CaF2 powder, nano Zn powder, nano Cu powder and nano Ag powder, and the average particle size is 5-500nm.
5. The SiC fiber containing Ti3SiC2 according to claim 1, characterized in that In the spinning precursor, the titanium source accounts for 1-70% of the mass of the polycarbosilane precursor, and the auxiliary agent accounts for 0.5-20% of the mass of the titanium source.
6. The SiC fiber containing Ti3SiC2 according to claim 1, characterized in that The strength of the SiC fiber containing Ti3SiC2 is ≥1.5GPa, and the modulus is ≥150GPa; after electrical performance testing, the electrical conductivity of the SiC fiber containing Ti3SiC2 is ≥2000S / m; The wave absorption performance was tested by a vector network analyzer and the minimum reflection loss RL of the SiC fiber containing Ti3SiC2 was ≤-8dB.
7. A method for preparing SiC fiber containing Ti3SiC2 as claimed in claim 1, characterized in that: The preparation method comprises: (1) Spinning: Spinning a spinning precursor including a polycarbosilane precursor, a titanium source, and an additive to obtain a precursor fiber; (2) Infusibility: The precursor fiber in (1) is infusible to obtain infusible fiber; (3) High temperature sintering: The infusible fibers in (2) are sintered at high temperature in a protective atmosphere to obtain SiC fibers containing Ti3SiC2.
8. The method for preparing SiC fiber containing Ti3SiC2 according to claim 7, characterized in that: The spinning in (1) includes one or more of melt spinning, dry spinning, and electrospinning.
9. The method for preparing SiC fiber containing Ti3SiC2 according to claim 7, characterized in that: The infusibility in (2) includes one or both of air infusibility and electron beam crosslinking; the temperature of air infusibility is 150-250°C, the time is 1-20 hours, and the atmosphere is flowing air; the total irradiation dose of electron beam crosslinking is 2-20 Mgy, the time is 1 minute to 10 hours, and the atmosphere is a flowing protective atmosphere.
10. The method for preparing SiC fiber containing Ti3SiC2 according to claim 7, characterized in that: The temperature of the high temperature sintering in (3) is 800-1600° C., the time is 0.1-10 h, and the protective atmosphere includes one of nitrogen atmosphere and inert atmosphere or a combination of the two.
Citation Information
Patent Citations
Preparation of substantially crystalline silicon carbide fibers from polycarbosilane
CA2033656A1
Method for preparing Ti3SiC2-based powder
CN102050448A
Silicon carbide fiber and preparation method thereof
CN113235189A
Preparation of substantially crystalline silicon carbide fibers from polycarbosilane
EP0438117A1
Ti3SiC2 COATING COMPOSITION AND COATING METHOD USING THE SAME
KR1020170086270A
Cited By
High-temperature heat-insulation noise-reduction bent ceramic fiber and preparation method thereof
CN119710984A
SiC / Ti3SiC2 radar wave-absorbing material as well as preparation method and application thereof
CN121851988A